Information systems for decentralization of development planning: managing the change process - Mohamed, Mohd Zain; Appalanaidu, U. B. (Elsevier, 1998)
The purpose of this study was to determine the extent of delegation of authority by the central government to the state and district level government in planning the development projects in Malaysia. Data for this research were obtained from structured questionnaires delivered by mail to a selected sample of respondents as well as from secondary sources such as previous studies and relevant government reports. The sample organizations were comprised of government ministries, central agencies, state development offices, and district offices. The results show that the central government has successfully delegated its authority to the state and district levels to the extent of operational and tactical planning as well as decision making. The efforts at decentralization have resulted in greater participation in developmental activities and more effective and efficient administration of development projects. To further enhance the development planning process, the government has introduced computerized information systems known as SETIA and SIAP which have increased the capacity for planning and implementation of the development projects. This demonstrates that the success of the projects depends heavily on careful planning, implementation, and optimal utilization of the resources allocated.